FORMULATING PRINCIPLES OF ISLAMIC PROSELYTIZATION: A SOCIOLOGICAL CONTRIBUTION - Syam, Nur (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper examines the contribution of sociology to the Islamic proselytization. In the context of epistemology, it has the opportunity to develop based on five aspects: factors, systems, interpretative, developmentalism and participatory. The five principles can be developed based on sociological theories. Among these theories, for example are the phenomenology of Islamic proselytization, the social construction of Islamic proselytization, dramaturgy of Islamic proselytization, hermeneutics of Islamic proselytization, communicative acts of Islamic proselytization, and ethnomethodology of Islamic proselytization. Through a sociological approach, the Islamic proselytization will be able to develop more quickly. In further, it can be said that the inclusion of social science is a form of pattern of science development based on the integration of science, namely the phenomenon of Islamic proselytization as an object of study and utilizing other sciences as an approach.